2006
DOI: 10.1111/j.1365-2133.1995.tb05023.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous infiltration in T-cell prolymphocytic leukaemia

Abstract: Summary T‐cell prolymphocytic leukaemia (T‐PLL) is an aggressive leukaemia accounting for over 30% of all mature T‐cell malignancies. We describe the clinical manifestations and histology of cutaneous involvement in a series of 92 patients with T‐PLL. Of the 92 patients. 26 (28%) had cutaneous involvement, and in 23 this was present at the time of the diagnosis of the leukaemia. Skin manifestations included a diffuse infiltrated erythema, infiltration localized to the face and ears, nodules and erythroderma. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 9 publications
1
41
0
Order By: Relevance
“…From a clinical perspective, prominent facial involvement, with or without associated swelling, was characteristic, having been described in other reports. 7,8 In the series by Mallet et al, 7 15% of their patients had localized erythema involving the face and ears. None of our patients had erythroderma, consonant with most other descriptions, 9 although the series by Mallet et al found erythroderma in 11.5% of their patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…From a clinical perspective, prominent facial involvement, with or without associated swelling, was characteristic, having been described in other reports. 7,8 In the series by Mallet et al, 7 15% of their patients had localized erythema involving the face and ears. None of our patients had erythroderma, consonant with most other descriptions, 9 although the series by Mallet et al found erythroderma in 11.5% of their patients.…”
Section: Discussionmentioning
confidence: 96%
“…3,5,6 One of the characteristic features of T-PLL is cutaneous involvement; the reported incidence is between 25% and 30%. 7 We describe six cases of T-PLL, in which skin involvement was an integral part of the clinical presentation, underscoring its frequent cutaneous tropism. The clinical, morphologic, phenotypic, molecular, and cytogenetic features of the skin involvement in these six cases are discussed.…”
Section: T -Cell Prolymphocytic Leukemia (T-pll) Is a Distinctive Formentioning
confidence: 96%
“…Multiple prominent highendothelial venules are often infi ltrated by neoplastic cells (10). Skin involvement diff ers from that seen in mycosis fungoides and Sézary syndrome, with dermal infi ltrates primarily around the appendages and without epidermotropism (7,15).…”
Section: Discussionmentioning
confidence: 99%
“…Skin disease has been reported at the time of initial diagnosis or later, heralding aggressive clinical course in such cases. The various cutaneous manifestations include facial swelling with erythema, alopecia, symmetrical petechial rash in the periorbital area, nodules and erythroderma [7,9]. Cutaneous histological features include grenz zone, dermal peri-vascular and peri-appendegeal infiltrate composed of medium-sized lymphoid cells with prominent nucleoli, similar to peripheral blood smear examination.…”
Section: Discussionmentioning
confidence: 93%
“…The characteristic clinical features of TPLL include splenomegaly, lymphadenopathy, skin disease and a high leukocyte count. The cutaneous features occurred in 25-28% of cases of TPLL in various case series [7,8]. Skin disease has been reported at the time of initial diagnosis or later, heralding aggressive clinical course in such cases.…”
Section: Discussionmentioning
confidence: 99%